The implementation of Lean Six Sigma : a case study of Multinational Corporation in Malaysia - Siti Salimah binti Jalal (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2019)
Lean Six Sigma (LSS) is a method focused on continuous improvement of quality, elimination of waste and minimization of defects in an organization. LSS has been tremendously applied in Multinational Corporation (MNC) for cost savings and benefits. Many LSS studies have been done in the western countries and a few studies has been found in developing countries particularly in plantation industries. This study aims to explore the process of implementation of LSS in one of the Malaysia MNC namely Palma, Somerset Bhd. In this study, the Palma division, one of the biggest plantation industries and the highest revenue contribution for Somerset Bhd, was examined as a single case study using a qualitative method. The data was collected by interviewing thirteen (13) executives and non-executives, documents reviews, and direct observations. Drawing on Actor-Network Theory (ANT), it was used to understand how a group of actors aimed to encourage other participants in implementing LSS by developing few strategies such as promotions and increments of work place. By strengthening the interest of the alliance and the relations between actors and other relevant actors within the network participation, hence, there is strong allies and network which support the implementation of LSS. Overall, this study contributes the process, benefits and the issues arise when implementing LSS particularly in plantation MNC in developing countries.